Can Cell-type specific variability be involved in a rare variant of Unverricht-Lundborg? Investigation with iPSC generated models - Duarte, Ana Joana (2022)
We thank the collaboration of colleagues who previously contributed to this work, as well as the ULD family; and INSA’s colleagues from DGH, particularly from the group of R&D/SA